Sigmoid function in the space of univalent function of Bazilevic type - Olatunji, S.O; Gbolagade, A.M; Anake, T; Fadipe-Joseph, O.A (Scientia magna, 2013)
Activation function is an information process that is inspired by the way biological nervous system such as brain, process information. Olatunji et al investigate the coefficient bounds of the class T... as related to the dass of modified Sigmoid activation functions. (ProQuest: ... denotes formulae/symbols omitted.)